p47Phox/CDK5/DRP1-Mediated Mitochondrial Fission Evokes PV Cell Degeneration in the Rat Dentate Gyrus Following Status Epilepticus - Kim, Ji-Eun; Kang, Tae-Cheon (Frontiers in Cellular Neuroscience, 2017)
Parvalbumin (PV) is one of the calcium-binding proteins, which plays an important role in the responsiveness of inhibitory neurons to an adaptation to repetitive spikes. Furthermore, PV neurons are highly vulnerable to status epilepticus (SE, prolonged seizure activity), although the underlining mechanism remains to be clarified. In the present study, we found that p47Phox expression was transiently and selectively increased in PV neurons 6 h after SE. This up-regulated p47Phox expression was accompanied by excessive mitochondrial fission. In this time point, CDK5-tyrosine 15 and dynamin-related protein 1 (DRP1)-serine 616 phosphorylations were also increased in PV cells. Apocynin (a p47Phox inhibitor) effectively mitigated PV cell loss via inhibition of CDK5/DRP1 phosphorylations and mitochondrial fragmentation induced by SE. Roscovitine (a CDK5 inhibitor) and Mdivi-1 (a DRP1 inhibitor) attenuated SE-induced PV cell loss by inhibiting aberrant mitochondrial fission. These findings suggest that p47Phox/CDK5/DRP1 may be one of the important upstream signaling pathways in PV cell degeneration induced by SE via excessive mitochondrial fragmentation.